2012
DOI: 10.1155/2012/276012
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Sequestration with Renal Aplasia and Elevated SUV Level in PET/CT

Abstract: Extralobar sequestration with other bronchopulmonary malformations is commonly seen; however, the association of extralobar sequestration with renal aplasia is very rare. A 75-year-old female patient was admitted with back pain. Ultrasonography revealed aplasia of the left kidney and tomography showed 6 × 4.5 cm sized tumor in the left hemithorax at the posterobasal area. The lesion has focally increased glycolytic activity (SUVmax: 3.2) at the left upper pole on positron emission tomography scan (PET/CT). Seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…However, research studies rarely report the false positive 18F-FDG PET observed in pulmonary sequestration and only a few false positive cases using 18F-FDG PET/CT have been reported. [ 9 12 ] Median SUV in these patients was 5.83 ± 4.729 which suggested malignancy, and SUVmax in this case is as high as 11.29. Interestingly, 2 of them were extra pulmonary sequestration, and the others were cases of intrapulmonary sequestration combined with pneumonia.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…However, research studies rarely report the false positive 18F-FDG PET observed in pulmonary sequestration and only a few false positive cases using 18F-FDG PET/CT have been reported. [ 9 12 ] Median SUV in these patients was 5.83 ± 4.729 which suggested malignancy, and SUVmax in this case is as high as 11.29. Interestingly, 2 of them were extra pulmonary sequestration, and the others were cases of intrapulmonary sequestration combined with pneumonia.…”
Section: Discussionmentioning
confidence: 70%
“…Importantly, the abnormal blood supply from one or more anomalous systemic arteries to the pathological tissue is helpful for the clinical diagnosis (Table 1 ). [ 9 12 ]…”
Section: Introductionmentioning
confidence: 99%